A Potential Protocol: Bridging community education and digital platforms for evaluation during online season / Siti Salwa Talib ... [et al.] - Talib, Siti Salwa; Md Noor, Nadia Wasila; Azri, Muhammad Azwan; Mohd Ali, Nathrah; Abdul Razak, Nurul Izzah; Rahimi, Muhammad Radhi; Baharudin, Nur Sakinah (2021)
Introduction: Occupational Therapy program learning outcomes achieved by learning in campus and in clinical setting. Both teach and assess students’ cognitive, psychomotor and affective domains. Measuring students’ ability on cognitive domain level four, analytical in the campus is difficult without access to a real patient. To reduce students' transition time into clinical setting, and to increase student ability to transfer knowledge and skills from campus into clinical setting are reasons for this project. The objective is to create a standard learning and evaluation protocol assessing students via community education and digital platform. The digital platform used are YouTube channel and Facebook. Communication between lecturer, and students via WhatsApp and google drive. Content for community education is a pre-recorded video. This is a report of experience using community education and digital platform to evaluate students’ cognitive domain level four. Methods: The project began by developing ideas and identify communities in need. Students were given a consent form to share their videos in the YouTube channel and Facebook. Instruments were created, a rubric to assess students, a feedback form for viewer response and questions for students' reflection. Therapy skills for the video are part of the lesson. Students created their storyboard, content and community association verified by the lecturer. Results: Responses received from 343 viewer, 97.7 to 99.7 % of the respondents answer it is beneficial for them. The rest is opposite. Students reflect positively the experience into teamwork, self-efficacy and identify need for skills in video editing. Learning time takes 12-16 hours. Conclusion: The result suggested a flow of the process is a success and can be adapted as a protocol for community education and digital platform. However, further research is needed for psychometric properties on rubrics, and identify long-term community needs. Commercialization potential may be possible for the protocol and skills video made.